2009 Fifth International Joint Conference on INC, IMS and IDC 2009
DOI: 10.1109/ncm.2009.224
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Flow Prediction with a Time-Oriented ARIMA Model

Abstract: The prediction of the traffic flow can give the people important traveling information. In this paper, the traffic flow prediction problem is studied. An ARIMA model is proposed for the traffic flow prediction. The ARIMA model is trained according to the different period traffic data. Based on the different period data training, the ARIMA model is refined more accuracy. The experiments show that the ARIMA model trained by the time-oriented data can reach a better result than the non time-oriented data trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…• HA: The historical average method calculates average value of each input as prediction, and compares the prediction with the true values of the next time steps. • ARIMA [3]: Auto-Regressive Integrated Moving Average(p,d,q) is a typical method using the degree of difference Table 1 summarizes the main results of all the methods on the test set. For each model, we fix the hyperparameters when it reaches the optimal performance on the validation set.…”
Section: Experimental Study 41 the Datasets And Settingsmentioning
confidence: 99%
“…• HA: The historical average method calculates average value of each input as prediction, and compares the prediction with the true values of the next time steps. • ARIMA [3]: Auto-Regressive Integrated Moving Average(p,d,q) is a typical method using the degree of difference Table 1 summarizes the main results of all the methods on the test set. For each model, we fix the hyperparameters when it reaches the optimal performance on the validation set.…”
Section: Experimental Study 41 the Datasets And Settingsmentioning
confidence: 99%
“…Time series [3], and neural network models [4] [5], are often applied to prediction traffic flow and predict traffic congestion based on vehicle speeds, weather, incident, and special days of historical data. Some studies use a Bayes classifier to predict traffic congestion [6] [7].…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…The nonparametric techniques include nonparametric regression [4] and neural network [5][6][7][8][9][10][11][12][13][14][15][16]. The parametric techniques include linear and nonlinear regression, historical average algorithms [6], smoothing techniques [6,11,17], and autoregressive linear processes [3,7,11,[17][18][19][20][21][22][23][24][25][26]. It is reported that the time series analysis based techniques like the autoregressive integrated moving average (ARIMA) is one of the most precise methods for the prediction of traffic flow when compared to other available techniques as mentioned above [27].…”
Section: Introductionmentioning
confidence: 99%
“…Mai et al [27] used 15 min aggregated traffic volume observations over a period of 26 days for fitting the SARIMA based traffic flow prediction model. Dong et al [25] used 2 months of flow observations aggregated to 5 min. intervals as input to ARIMA model for predicting the flow for the test day of interest.…”
Section: Introductionmentioning
confidence: 99%